(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
Family businesses which are often adjudged very risky ventures as a result of rapid decision makings are quite different from other enterprises, as they contribute immensely in wealth creation, economic development, sustainability, employment and job opportunities, improved Gross Domestic Product, prospect from younger generations, as well as mentorship from experienced business leaders. However, despite their numerous contributions, they are often bedeviled by numerous challenges which often lead to their failures at the exit or death of their founders. This paper identified the rate of family businesses that have suffered generational transition failures in Anambra state, and also examined the differences in personal characteristics of founders of both failed and prospered Generational Transition (GT) family businesses in the state. The application of Taro Yamane formula gave a sample size of 327, a total of 327 questionnaires was therefore administered to Directors and Managers of Family businesses in the three main cities of Anambra state. The results of the study revealed that 72 percent of the family businesses fail after generational transition. Also, the analysis based on the mean of the individual questionnaire items, with the acceptance benchmark of 3 revealed that there are significant differences in the personal characteristics of the founders of the failed and successful generational transition family businesses. The regression analysis validated the results as indicated by the correlation coefficient (R = .868). It could also be observed from the coefficient of determination (R-Square = .792) that 79 percent differences exist in the relationship between the personal characteristics of founders of the failed and prospered GT family businesses in the state. The paper concluded that founders and Directors of FBs should adopt positive personal characteristics, in order to mitigate the high failure rates of family businesses.